A-8 EFFECT OF CALCINATION TEMPERATURE ON MICROSTRUCTURE AND PHASE FORMATION OF Ba (Zr_xTi_<1-X>)O_3 POWDERS(Session: Ceramics II) - Nalinee Phungjitt; Naratip Vittayakorn; Theerachai Bongkarn (My University, 2006)
In this work, the effect of calcinations temperature on microstructure and phase formation of Ba(Zr_xTi_<1-X>)O_3 powders was investigated. The BZT powders were prepared via the solid state reaction method under various calcinations temperatures. The pure perovskite phase of the BZT powders was obtained with calcinations condition at 1,300℃ for 4 h. The TGA and DTA results were corresponding to XRD investigation. The microstructure of the powders exhibit an almost-spherical morphology and have a porous agglomerated form.
Keywords: Ferroelectric and Piezoelectric Materials